Welfare-based monetary policy rules in an estimated DSGE model of the US economy - Michel Juillard; Philippe Karam; Douglas Laxton; Paolo Pesenti (European Central Bank (ECB), 2006)
We develop and estimate a stylized micro-founded model of the US economy. Next we compute the parameters of a simple interest rate policy rule that maximizes the unconditional mean of utility. We show that such a welfare-based rule lies close to the Taylor efficiency frontier. A counterfactual analysis assesses to what extent using such a rule as a guideline for monetary policy would have helped to avoid the inflationary swings of the 1970s and reduce the severity of boom and bust cycles. The paper also provides estimates of the welfare implications of business cycle variability and discusses their relevance.
Keywords: C51; E31; E52; 330; competition; Markups; monetary policy; Taylor Rule; Geldpolitik; Taylor-Regel; Makroökonometrie; Wettbewerb; USA